Mapping of Land Use Suitability for Binjai City in 2020-2024 Using SPOT-6 Imagery - Darwin Parlaungan Lubis; Yessi Karolina Marbun; M. Taufik Rahmadi; Mahara Sintong; Sendi Permana; Alvin Pratama (Department of Geography Education, University of Jember, 2024)
Indonesia is a developing country that experiences high population growth every year. Population growth has an impact on the high demand for land use. Land use is often not in harmony with population growth, so land use does not align with regional spatial conditions. This study aims to determine land use in 2021 in Binjai City based on the 2020-2040 Regional Spatial Plan (RTRW) using Spot 6 imagery and determine the suitability of 2021 land use in Binjai City based on the 2020-2020 Regional Spatial Plan (RTRW) 2040 using Image Spot 6. This study is located in Binjai City, administratively flanked by two significant regencies: Langkat Regency and Deli Serdang Regency. The population of this research is the City of Binjai, with an area of 90.23 km2. Data collection techniques are documentation study techniques, image interpretation, and field observations. Data analysis was carried out in a qualitative descriptive manner. The results of the study show that Land use in Binjai City in 2021 includes an agricultural area of 52.93 km2 with a percentage of 58.66%, then a residential area of 33.85 km2 with a percentage of 37.63%, area conservation has an area of 1.58 km2 with a percentage of 1.75%, river bodies have an area of 0.90 km2 with a percentage of 1%, local protected areas have an area of 0.38 km2 with a percentage of 0.39%, defense and security areas have an area of 0.45 km2 with the percentage of 0.42%, industrial designation area of 0.12 km2 with a percentage of 0.15%, tourism area of 0.01 km2 with a percentage of 0.01%, and lakes/situ area of 0.01% 0.01 km2 with a percentage of 0.01%. The suitability of land use in 2021 with the Binjai City Spatial Plan (RTRW) for 2020-2040 is an area of 43.64 km2 with a percentage of 48.36% which is suitable while that which is not suitable is 46, 59 km2 with a percentage of 51.64%.